Amyand's hernia in a preterm infant: Case report and literature review - Vicky Lu; Kai-Hsiang Hsu; Yung-Ching Ming; Ming-Chou Chiang (Elsevier, 2023)
Introduction: Amyand's hernia (AH) is a rare type of inguinal hernia that occurs when the appendix is trapped within the hernia sac. AH accounts for approximately 1% of all inguinal hernias. However, there is currently no comprehensive review on the manifestation of AH in preterm infants. Case presentation: A male preterm infant, born at 31+5 weeks' gestational age with a birthweight of 1040 g, presented with a right inguinal mass at 39 days of life. The inguinal mass was firm, irreducible and erythematous. The infant also exhibited symptoms of fever and poor feeding. An abdominal X-ray showed an obstructive ileus consistent with clusters of cyst-like gas bubbles suggesting pneumatosis intestinalis. Recognizing the urgent need for intervention, emergent surgery was performed. A transverse incision along the right inguinal crease. An intraoperative exploration revealed a gangrenous appendix within the hernia which indicating AH. Herniorrhaphy and appendectomy were successfully performed without any postoperative complications. Feeding was resumed 8 days after the surgery, and the infant was discharged soon with full recovery. Conclusion: AH is characterized by an irreducible inguinal mass that is predominantly found on the right side in preterm infants, especially males. In less mature infants, the manifestation of AH may be more severe. Therefore, AH should be considered in the differential diagnosis of infants with abdominal emergencies, and careful intra-operative assessment is essential. AH typically requires less complex treatment and has a favorable prognosis compared to other abdominal conditions in preterm infants.